Assessment of Bambusa vulgaris Schrad. ex J.C.Wendl. as potential phytoremediation agent for heavy metals - Wan Abdul Rahim, Wan Rafiekal (2016)
Heavy metal pollution had becoming one of the most serious environmental problems today. These pollutants have highly affected agricultural productivity, human health as well as disrupting the world’s ecological biodiversity system. Experimental research conducted had undergone the phytoremediation process which is bio-based low cost alternative technology, environmental friendly and represents the efficiency of using plants for treatment of heavy metal. Bamboos are potentially good plants for phytoremediation due to their widespread distribution, simple and well-known propagation mode, the full range of species and their potential as an additional use for raw material. They are fast-growing, grow more rapidly than other timber species and have various actual and possible applications for income generation and environmental conservation. This study aims in evaluate the potential of B. vulgaris as phytoremediation agent for heavy metal. The plants were grown up uniformly in lysimeter pot for three months in the presence of heavy metal copper, zinc and iron with different level of concentration to quantify the toxic effects of these metals on morphological and physiological attributes of B. vulgaris. Leachates from lysimeter were being collected periodically and undergoing screening process to determine the contents of remaining heavy metal in samples. The close positive relationship of heavy metal analysis that exhibits low concentration of metal before and after treated or infiltrated by B. vulgaris indicates that it can be used as bioaccumulator plants of heavy metal pollution by absorbing excess heavy metal from the polluted soils and water. From the study, B. vulgaris most efficient in uptake iron compared to zinc and copper. The findings indicated that heavy metals copper zinc and iron are considered to be important for plant growth due to the positive response in morphological and physiological attributes of B. vulgaris at low concentration however brings phytotoxicity effects at high level of concentration and time. B.vulgaris performance was increased at early weeks and in low concentration metal level indicated it’s tolerance to the heavy metals, making it a prospective phytoremediator species. Thus, we can conclude that B. vulgaris has potential to be a phytoremediator plant and can be grown up on moderately heavy metal contaminated soil.